Violência física e psicológica no trabalho da Enfermagem - Lima, Gustavo Henrique Alves (2014)
The violence at work is understood as an incident in which the employeer suffer abuse, threat or attack in circumstances related on his work, including in the path of return to the same, involving an explicit or implicit threat to their safety, health or welfare. The research has as main objective to investigate practices of physical and psychological violence between staff, in relations between patients, caregivers and other professionals with the nursing staff of the public hospital of Caxias-MA. This is a descriptive research with quantitative character and epidemiologic approach. The study population was composed of nurses, technicians and nursing assistants who work in the public hospital of the county. The data collection was realized in the city of Caxias-MA from november 2013 to may 2014. The data were collected through a form comprised of closed questions. The analysis was performed using SPSS software for demonstration of results in absolute numbers and percentages in the form of graphs and tables. The numerical variables were calculated and shown by average; the categorical variables were demonstrated by frequency and percentage. As results, 124 employees of nursing participated in the survey (37% of the population), it was found that the investigated workers are relatively young and predominantly female and married. The category that suffered most violence were the nurses 76% (19), followed by technicians 72% (57) and nursing assistants 60% (12). The psychological violence was most frequent among all studied, being verbal violence of its subtype most frequently 95% (84), then followed by physical violence 31% (27), bullying 27% (24), sexual harassment 9% (8) and racial discrimination 9% (8). The patients are the main perpetrators of violence with 60% (53) of cases, followed by their relatives 32% (28), co-workers of the same hierarchical level of 31% (27), administrators/ managers 20% (17) and doctors 12% (11). The sectors with the highest occurrence of violence were emergency 30% (45) and medical clinic 29% (44). Concludes that the category that suffer most violence at work are nurses, the psychological violence along with its subtype verbal aggression are the most affect workers, being the patient the main perpetrator. The emergence is the sector with the highest occurrence of violence, the workers react to the psychological violence try to pretend that nothing has happened or become unresponsive and in the case of physics violence, try to defend yourself physically. The biggest repercussions of violence are psychological and the employers do not so much about this situation, thus, is important to research and study more about the theme in order to promote reflection by all involved in this problem.